Intragroup processes and teamwork within a successful chamber choir. (2nd October 2017) - Kirrane, Melrona; O'Connor, Cliodhna; Dunne, Ann-Marie; Moriarty, Patricia
ABSTRACT: Despite the ubiquity of choirs across time and cultures, relatively little is known about the internal dynamics of these social systems. This article examines the group processes involved in a small European chamber choir. The research adopted a mixed-methods qualitative approach that combined individual interviews ( n = 13) with ethnographic observation. Analysis described the group processes of the choir in relation to standard models of effective teamwork. The results suggest that certain dynamics of this choir lie beyond conventional conceptualisations of teamwork. Further conceptual and empirical research is necessary to develop a model of teamwork that can be applied to the conditions of performance-based teams and inform choral practice and training.